ASSESSMENT OF GROUNDWATER QUALITY AND CHARACTERISTICS FORMATION IN PHREATIC AQUIFERS IN AHOADA WEST L.G.A, RIVERS STATE, NIGERIA - Oyintare Brisibe; Owonaro B. Jennifer; Jamiu A. Sikiru; Timiyan T. Kingsley; Akosubo I. Stevyn (International Journal Of Advance Research And Innovative Ideas In Education, 2022)
The research was to find a better solution to pollution transport in groundwater, considering the effect of geologic parameters such as heavy metals, micronutrients, porosity, permeability, and void ratio. The source of pollution was through indiscriminate dumping of biological wastes and wastes from soakaway, regenerating the wastes in most parts of the study area. This research was carried out through an experiment performed for E. coli transport, including some other parameters that influence microbial growth, inhibition and variation for fast migration within a short period of time. These parameters are heavy metals, micronutrients, permeability, porosity, and void ratio. The physiochemical parameter from the study carried out found that the growth of E. coli under environmental conditions favoured it. The research was able to produce the level of physiochemical parameters influencing E. coli concentration in groundwater. The presence of E. coli depends on the availability of nutrients as well as favourable conditions in terms of physicochemical parameters. The study confirmed that the higher the depth of water, the lower the population of E. coli in some locations based on the decrease in substrate utilization; while in some areas, it varies. The study carried out was able to express the stabilization of groundwater quality by inhibiting the presence of metallic element in some locations; while in a few locations in the study area, it was discovered that the presence of E. coli in different aquifers have a lower percentage and become less harmful to the quality of groundwater for human utilization. The level of porosity was investigated on the migration of E. coli influenced by porosity from one aquifer to the other, the results were calibrated and verified generating a model that can be applied to predict the rate at which E. coli transport within a short period of time.
Keywords: Groundwater; Water Quality; Phreatic Aquifer; E. coli; Transport Mechanism; Ahoada West L.G.A.; Rivers State